Acceptor and donor one-pot voltage-activated adhesives - Tan, Nigel Chew Shun (Nanyang Technological University, 2021)
Recent research has shown the voltage-activated adhesives are limited to water-based solvents. Non-conductive environment and high solvent resistance from the organic solvents are the main causes that lead to difficulty in curing of adhesive by voltage activation. On the contrary, curing the adhesive in water-based solvents like phosphate-buffered saline (PBS) results in no issue with voltage activation. However, water electrolysis occurs during voltage-curing. The generation of oxygen and hydrogen gases causes excessive foaming that compromises the structural properties of the adhesive. Thus, the advantages of replacing the water-based solvent with organic solvent are not limited to the adhesive application but can expand to other applications such as cosmetics and flexible implantable biosensors. Co-grafting the conductive additive ferrocene (Fc, donor) and the crosslinker diazirine (Dz, acceptor) onto the G5-PAMAM dendrimer in a biocompatible organic solvent (DMSO) can result in a donor-acceptor dendrimer. Fc is oxidized to Fc+ (donor) and provides a conductive hole network, while Dz is reduced to Dz- (acceptor). Dz is oxidized to form carbenes, leading to intra/intermolecular crosslinking adhesion when voltage activation occurs. However, high donor-acceptor ratios co-grafted into one dendrimer leads to insolubility in organic solvents. Therefore, donor-acceptor blends overcome solubility limitations and provide faster throughput of structure-activity relationships with less synthetic investment. Despite these advantages, blend adhesives are constrained to intermolecular crosslinking adhesion upon voltage activation. In addition, the voltage activation concept of donor-acceptor pairs was not limited to ferrocene/diazirine designs. The concept was extended to donor-acceptor pairs containing catechol and a Schiff base, which crosslinked upon voltage activation. However, catechol adhesives are susceptible to air oxidation, which leads to short shelf-stability. Thus, further work may explore catechol variants, such as vanillin, to resolve the problem of shelf-stability while retaining donor-acceptor electrocuring. This thesis demonstrates the first proof-of-concept voltage-activated adhesive in organic solvents with donor-acceptor functional groups that can be initiated at low voltages (-1V to -5V, Ag/AgCl). This could contribute to the development of stimuli activated bioadhesives, drug delivery methods, cosmetic coatings, flexible implantable biosensors, and industrial on-demand adhesives.